Rental Service Market of Farm Machinery in Rice Cultivation: A Farm Level Investigation - Islam, AKMS; Kabir, MJ (Bangladesh Rice Journal, 2018)
This study was undertaken to investigate the rental charge and labour cost of five major operations in rice production in the north-west region of Bangladesh. Farmers’ group discussions (FGDs) with 10-15 key informants farmers were conducted for collecting farm level data from 15 villages of both Rajshahi and Rangpur divisions. Rental charge and labour cost of rice cultivation were converted to paddy equivalent cost (PEC) for tillage, transplanting, weeding, harvesting, carrying and threshing. Farmers mostly relied on the service providers of either power tiller or tractor for tillage. They also relied on the service providers of close drum power thresher for threshing rice and other crops. However, farmers still manually carried out transplanting, weeding, harvesting and carrying of rice. Both the contractual and daily basis hired labour and family labour performed those activities. The wages of labour of harvesting and carrying was paid in cash or kind (e.g., share of harvested grain or fixed amount of grain per unit of harvest area). The average paddy equivalent cost for the five major operations was ranged between 37-47% of total paddy production cost in the study locations. The mechanized transplanting and harvesting may reduce rice production cost largely as well as would resolve the labour scarcity problems. Therefore, transplanter and harvester have the great prospect of widespread adoption. However, prospect of mechanical weeding is limited because of the availability of low cost intensive chemical control methods. Thus, providing the larger financial assistance on purchasing both the transplanter and harvester facilitates the end users to enhance the productivity and reduce the cost of rice farming. Bangladesh Rice j. 2017, 21(1): 35-45